(PKM) Donor Darah Di Lingkungan Universitas Pertahanan RI - Saragih, Hondor; Pannyiwi, Rahmat; Mainassy, Meilisa Carlen (Asosiasi Guru dan Dosen Seluruh Indonesia, 2024)
In the context of the XVth Anniversary of the Indonesian Defense University, the Blood Donation Unit is collaborating with the Blood Donor Unit which is a work unit at PMI Bogor city which is tasked with carrying out activities related to blood donation and blood requests. In this case, PMI Bogor City can be said to be very successful in terms of blood production levels. This blood donation activity is a collaboration between the Faculty of Medicine and Health Sciences, Defense University of the Republic of Indonesia and the Indonesian Red Cross of Bogor City in the context of the XVth Anniversary of the Republic of Indonesia Defense University in donating blood. This activity aims to help others, especially those in conditions that require an external blood supply, because until now blood cannot be synthesized so when it is needed it must be taken by someone/individual and also to empower human resources to take a leadership role in influencing positive thought patterns, attitudes. and behavior in their communities towards a culture of respect for diversity, intercultural dialogue, gender equality, youth social issues and peace. This activity was held at the Red and White Hall Building, UNHAN RI Campus, Sentul, Bogor Regency, West Java.